Effects of TNFR1 gene silencing on early apoptosis of marbofloxacin-treated chondrocytes from juvenile dogs. (15th June 2019) - Li, Qiao; Ding, Yi; Gao, Yuan; Zhang, Futao; Zhu, Hongmei; Ding, Mingxing
Highlights: TNF/TNFR1 signaling pathway was involved in the early apoptosis of marbofloxacin-induced chondrocytes. Marbofloxacin induced apoptosis rates of the chondrocytes in a concentration- and time-dependent manner. TNFR1 gene silencing by siRNA reference significantly decreased the chondrocyte apoptosis. Abstract: Quinolones (QNs)-induced cartilaginous lesions in juvenile animals by chondrocyte apoptosis is an important toxic effect, which results in the restriction of their use in pediatrics. However, limited data about QNs chondrotoxicity are available for evaluation of the potential toxicity in both animals and human cartilage. To explore whether tumor necrosis factor/its receptor (TNF/TNFR1) signaling pathway is involved in the early apoptosis of marbofloxacin-induced chondrocytes, canine juvenile chondrocytes were treated with 0, 20, 50 and 100 μg/mL marbofloxacin. Results showed that the apoptosis rates of the chondrocytes at 2, 8 and 24 h were significantly increased in a concentration- and time-dependent manner ( P  <  0.05). The mRNA levels of apoptosis-related factors in TNF/TNFR1 signaling pathways and the protein levels of TNFα and TNFR1 were increased in canine chondrocytes treated with 20–100 μg/mL marbofloxacin ( P  <  0.05) while TNFR1 gene silencing significantly decreased the chondrocyte apoptosis and inhibited the mRNA expression of TNF/TNFR1 downstream signaling molecules after 100 μg/mL marbofloxacin treatment at 8 h ( P  <  0.01). It was confirmed that activated TNF/TNFR1 signaling pathway may play a leading role in the early apoptosis of marbofloxacin-induced canine juvenile chondrocytes, which is helpful for clinical estimation or prevention of the risk of QNs.